1992
DOI: 10.1007/bf01973383
|View full text |Cite
|
Sign up to set email alerts
|

On the bioactivation and genotoxic action of fluoranthene

Abstract: Fluoranthene (FA) was studied with respect to possible mechanisms of its high mutagenicity but low carcinogenicity, in comparison with the corresponding properties of benzo[a]pyrene (BaP), and with regard to the synergism of these two compounds shown by van Duuren and Goldschmidt (J Natl Cancer Inst 56, 1976, 1237). FA and BaP activated by S9 from Aroclor 1254 (PCB)-treated rats induce HPRT mutations in CHO cells with about equal effectiveness at the same exposure doses, which also lead to the same frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
4
14
2
Order By: Relevance
“…Induction of CYP enzymes by BaP may have modulated the enzymatic metabolic activation of FLA thereby enhancing its carcinogenic potential. Our findings are in agreement with that of Vaca et al (1992) and Huderson et al (2010) who have shown that co-treatment with BaP induces the microsomal metabolism of FLA to precursors of reactive metabolites. Bio-tranformation of FLA by tumor cells may lead to production of intracellular metabolites (Buesen et al, 2002; Myers et al, 2011) whose production rate may have enhanced due to the action of BaP.…”
Section: Discussionsupporting
confidence: 93%
“…Induction of CYP enzymes by BaP may have modulated the enzymatic metabolic activation of FLA thereby enhancing its carcinogenic potential. Our findings are in agreement with that of Vaca et al (1992) and Huderson et al (2010) who have shown that co-treatment with BaP induces the microsomal metabolism of FLA to precursors of reactive metabolites. Bio-tranformation of FLA by tumor cells may lead to production of intracellular metabolites (Buesen et al, 2002; Myers et al, 2011) whose production rate may have enhanced due to the action of BaP.…”
Section: Discussionsupporting
confidence: 93%
“…These data are in agreement with other studies indicating that neither Fla nor Pyr was mutagenic or genotoxic γ H2AX fold induction 8 7 6 5 8 7 6 5 8 7 6 5 8 7 6 5 8 7 6 5 8 7 6 5 8 7 6 5 8 7 6 5 9 8 7 6 9 8 7 6 M 10 -X : (Vaca et al, 1992, Durant et al 1996Sjogren et al 1996). Although the carcinogenic potential of Fla is considered as equivocal (Wang and Busby, 1993;Wang et al, 1995;Stocker et al, 1996), both Pyr and Fla were classified as non-carcinogenic (IARC, 2010).…”
Section: Genotoxicity Of Pahs In Human Cell Linessupporting
confidence: 93%
“…Fluoranthene, like B[a]P, is metabolized to mutagenic DEs and its mutagenic potency is close to that of B[a]P (Vaca et al 1992). The carcinogenic action of fluoranthene diolepoxide has been demonstrated experimentally .…”
Section: Benzo[a]pyrene (Bp) (+)-Bp-78-epoxide (-)-Bp-78-dihydrodiomentioning
confidence: 99%
“…The carcinogenic action of fluoranthene diolepoxide has been demonstrated experimentally . In carcinogenicity tests with high doses, however, B[a]P is considerably more effective than fluoranthene (Busby et al 1984), evidently because of the promoter action of B[a]P (Vaca et al 1992). Although fluoranthene is now considered a weak carcinogen (WHO/IPCS 1998), the observed cancer incidence and the numbers of tumors per animal are compatible with linear doseresponse relationships (Wang and Busby 1993).…”
Section: Benzo[a]pyrene (Bp) (+)-Bp-78-epoxide (-)-Bp-78-dihydrodiomentioning
confidence: 99%